2008
DOI: 10.1108/00330330810892695
|View full text |Cite
|
Sign up to set email alerts
|

Digital libraries and repositories in India: an evaluative study

Abstract: PurposeThe purpose of this research is to identify and evaluate the collections within digital libraries and repositories in India available in the public domain.Design/methodology/approachThe digital libraries and repositories were identified through a study of the literature, as well as internet searching and browsing. The resulting digital libraries and repositories were explored to study their collections.FindingsUse of open source software especially for the creation of institutional repositories is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…In another study on OSS DL software, Mittal and Mahesh (2008) found that Dspace, GSDL and Eprints were used in the creation of DL and institutional repositories in India.…”
Section: Oss Solutions Inmentioning
confidence: 99%
“…In another study on OSS DL software, Mittal and Mahesh (2008) found that Dspace, GSDL and Eprints were used in the creation of DL and institutional repositories in India.…”
Section: Oss Solutions Inmentioning
confidence: 99%
“…There are numbers of digital repositories software available as "Open Source" as well as "Proprietary". Mittal and Mahesh (2008) discussed about using open source in setting up digital libraries. According to the above researchers employing open source software is very easy and they provide clear awareness, training facilities and most importantly the negligible costs.…”
Section: Digital Preservation and Its Importancementioning
confidence: 99%
“…While the strength of the links between domains varies, their evident connectedness supports the case for policy coordination, a case which is reinforced by explicit manifestations of interconnectedness across Open domains. For example, OA services, such as institutional repositories, commonly deploy OSS products, including D-Space and ePrints (Mittal & Mahesh, 2008;Pinfield et al, in press;Tedd, 2009). OA publication of research datasets alongside or embedded (interactively) in related journal articles, enabling validation of results (Rzepa, 2011;Shotton, 2012), is another manifestation of interconnectedness.…”
Section: Open Convergence and Coherencementioning
confidence: 99%